2013
DOI: 10.3390/molecules181114320
|View full text |Cite
|
Sign up to set email alerts
|

Tuning a 96-Well Microtiter Plate Fluorescence-Based Assay to Identify AGE Inhibitors in Crude Plant Extracts

Abstract: Advanced glycation end-products (AGEs) are involved in the pathogenesis of numerous diseases. Among them, cellular accumulation of AGEs contributes to vascular complications in diabetes. Besides using drugs to lower blood sugar, a balanced diet and the intake of herbal products potentially limiting AGE formation could be considered beneficial for patients’ health. The current paper presents a simple and cheap high-throughput screening (HTS) assay based on AGE fluorescence and suitable for plant extract screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 59 publications
2
56
0
13
Order By: Relevance
“…The mixture of hexane and ethyl acetate layers of a MeOH extract of Linaria japonica was fractionated by various types of chromatography to afford eight compounds (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mixture of hexane and ethyl acetate layers of a MeOH extract of Linaria japonica was fractionated by various types of chromatography to afford eight compounds (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, inhibitors of AGEs formation are demanded as potential therapeutic remedy. The inhibitory effects of the isolated compounds (1-8) on AGEs formation were evaluated using a fluorescent method 8,9) (Table 2). The results showed that new compounds 1, 2 and 3 showed stronger inhibitory activity (IC 50 =34.8, 35.0 and 19.5 µM, respectively) than that of a reference compound, aminoguanidine (1.29 mM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyphenols such as genistein, naringin, and ellagic acid are reported to control aldehyde-induced glycation and prevention of the formation of AGE precursors [15]. This work adapts a cost-effective high-throughput screening-based assay to identify the potency of aldose reductase inhibitors (ARIs), quercetin, and catechin in the prevention of early AGEs [16].…”
Section: Introductionmentioning
confidence: 99%